Penerapan Metode Weighted Product Pada Sistem Penentuan Dosen Pembimbing Dan Penguji Skripsi - Renny Puspita Sari; Ibnur Rusi; Ferdy Febriyanto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
The supervisor and thesis examiner for a student is very important because it acts as a guide, facilitator, and provides motivation. Determination of supervisors and examiners at the Department of Information Systems, Faculty of Mathematics and Natural Sciences (MIPA) is still being carried out through internal department meetings. This is less effective and efficient considering the large number of students who submit final assignments, the titles of students' final assignments are very diverse, as well as supervisors and examiners with different competencies. The final result of the system can show the ranking order of the supervisor and thesis examiners with the Weighted Product method, besides that this system will also provide information on the number of students being mentored, students being tested and the number of students who have been supervised by the lecturer concerned. The system can also print the minutes of the thesis implementation which are divided into proposal seminars, result seminars and undergraduate sessions which automatically include the names of the supervisors and examiners. With the construction of this system, it is hoped that it can help make it easier for the department to determine the supervisor and examiner of the final project and facilitate the administrative process of the final project in the Information Systems Department, Faculty of Mathematics and Natural Sciences, Tanjungpura University.